The Political Geography of Campaign Finance - Dowdle, Andrew. author. aut Link
XIII, 204 p. 36 illus.
Keywords: The Political Geography of Campaign Finance examines the distribution of political campaign contributions in the 2004, 2008, and 2012 preprimary election periods. Using aggregated individual level data, the authors determine if certain areas contribute more to presidential candidates in different stages of the campaign, and if these patterns are independent of wealth and partisanship. Unlike previous research, this book examines individual counties over multiple election cycles.